Bihar Third Five Year Plan Progress Report for the Period Ending December, 1964 - Planning Commission (Planning Commission, 1964)
Agricultural Programme, Co-Operation C. D. and Gram Panchayat, Irrigation and Flood Control, Power Industries and Mining, Transport and Communications, Social Services.
Bihar